Biomarker for renal scarring screening in children with vesicoureteral reflux: a systematic review - Putri, Utari Mudhia Arisa; Raharja, Putu Angga Risky; Situmorang, Gerhard Reinaldi; Wahyudi, Irfan; Rodjani, Arry; Puspitasari, Henny Adriani; Imam, Abubakr; Saraiva, Luis R.; Vallasciani, Santiago; Abbas, Tariq O. (Frontiers in Pediatrics, 2025)
IntroductionVesicoureteral reflux (VUR) is a prevalent pediatric urological condition that increases children's risk of urinary tract infections (UTIs) and renal damage. Renal scarring linked to VUR can lead to long-term complications, including hypertension and chronic kidney disease (CKD). Although traditional imaging techniques, such as dimercaptosuccinic acid (DMSA) scans, are regarded as the gold standard for identifying renal scarring, they come with risks of radiation exposure and high costs. This review investigates the diagnostic accuracy of blood and urine biomarkers as alternative methods for detecting renal scarring in VUR.MethodsThis systematic review adhered to the PRISMA 2020 guidelines. We conducted a comprehensive search across three databases—PubMed, ScienceDirect, and Cochrane—for studies on biomarkers associated with renal scarring in children with VUR. The included studies were evaluated for diagnostic accuracy (sensitivity and specificity) and assessed for risk of bias using the QUADAS-2 framework.ResultsNine studies met the eligibility criteria and were included in the qualitative synthesis. Biomarkers such as NGAL, CRP, CXCL8/IL-8, LL-37, and IL-6 were evaluated. Among these, urinary NGAL demonstrated the best diagnostic performance, with sensitivity ranging from 72%–84% and specificity between 60% and 81%. Other biomarkers exhibited moderate accuracy, although they were less reliable than NGAL. Overall, biomarkers present a promising non-invasive alternative to traditional imaging for detecting renal scarring in children with VUR.ConclusionUrinary biomarkers, particularly NGAL, hold potential for detecting VUR and renal scarring in children, providing a non-invasive alternative to traditional imaging methods. However, additional validation and standardization are necessary before these biomarkers can be routinely applied in clinical practice.